If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(2x+8)=6(x-2)
We move all terms to the left:
4(2x+8)-(6(x-2))=0
We multiply parentheses
8x-(6(x-2))+32=0
We calculate terms in parentheses: -(6(x-2)), so:We get rid of parentheses
6(x-2)
We multiply parentheses
6x-12
Back to the equation:
-(6x-12)
8x-6x+12+32=0
We add all the numbers together, and all the variables
2x+44=0
We move all terms containing x to the left, all other terms to the right
2x=-44
x=-44/2
x=-22
| -189=4x-3(-4x-15) | | -2.5(3.8x-1.9)=83.7 | | x^2(2x-14)=0 | | -6x=-104 | | 10x+5=x-5 | | 8m+2+2m=10m+2 | | 7(n-4)=3n-12 | | 5+3p=-1+4p | | 5(x-1)=-(2x+3) | | 5x+1x=33+9x | | -4x-3=37 | | 4x+2=-x+6 | | 2(m+2)=1£ | | 10x-4x-86=64 | | x=1/3x+2/3 | | -2x+4=-3x-5 | | 1+(-2/2x)=-8+(-1/7x) | | -2(v+5)=v-9+3(5v+1) | | -33=b+(-16) | | 10x+4=3+11x | | 360=37.50x+60 | | 2x−3 =5 | | -2x+4=-3x-6 | | 10x+5=x-6 | | 2x+8+2x+8=5x+11 | | L^2-2l-80=0 | | c/3+-9=-8 | | 4x-10=5x-50 | | 5k-2=2k+5 | | 20-v=20-13v+12v | | 4z+10=12+z | | 9x+31x-10=10(4x+10) |